2016
DOI: 10.17559/tv-20151028072528
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the teeth profile shape on polymer gear pair properties

Abstract: Original scientific paper The paper presents an extensive research on two different tooth-flank geometries, i.e. involute and S-gears. A significant difference between the two analyzed geometries was observed during the lifetime testing. The tests were conducted on special test equipment with an axis distance of 20 mm. The material used for the tested gears was POM for the driver gear and PA6 for the driven gear. The same sizes of driver and driven gears were used (m = 1 mm, z = 20). Gears of this size are par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 13 publications
(29 reference statements)
0
5
0
Order By: Relevance
“…At higher loads the typical failure mode can be similar: (ii) wear was e.g. observed on steel/POM, steel/HDPE (high-density polyethylene) and steel/POM pairs (Singh et al [6]), (iv) root fracture induced in this case by stress overload, as observed for POM/ PA6 pairs by Pogac ˇnik et al [7] and Duhovnik et al [8] and for steel/PA66 by Sarita et al [5]. In addition, permanent viscoelastic/viscoplastic strain accumulation (v) can also occur at higher loads, as identified on steel/PA66 pairs by Sarita et al [5] and on POM/PA66 pairs by Pogac ˇnik et al [7].…”
mentioning
confidence: 57%
“…At higher loads the typical failure mode can be similar: (ii) wear was e.g. observed on steel/POM, steel/HDPE (high-density polyethylene) and steel/POM pairs (Singh et al [6]), (iv) root fracture induced in this case by stress overload, as observed for POM/ PA6 pairs by Pogac ˇnik et al [7] and Duhovnik et al [8] and for steel/PA66 by Sarita et al [5]. In addition, permanent viscoelastic/viscoplastic strain accumulation (v) can also occur at higher loads, as identified on steel/PA66 pairs by Sarita et al [5] and on POM/PA66 pairs by Pogac ˇnik et al [7].…”
mentioning
confidence: 57%
“…In this case, a higher load capacity of the S-gears was measured. Results on research concerning polymer S-gears were published in several papers [82] to [85]. A comparison of the efficiency of S-gears and involute gears was made.…”
Section: S-gearsmentioning
confidence: 99%
“…Gears are essential elements in engineering. Ensuring their quality and ensuring optimal parameters of manufacturing is, therefore, crucial [1,2]. An accurate, holistic, and simple method of inspection is needed for accurately produced gears.…”
Section: Introductionmentioning
confidence: 99%